The impact of leader power on organizational development: a strategic approach to decision-making - Rosita, Sry; Tialonawarmi, Feny; Yacob, Syahmardi (Business: Theory and Practice, 2023)
Leaders play a pivotal role in shaping the trajectory of work programs and facilitating accomplishing of organizational goals. This study investigates the intricate relationship between leader power, decision-making, and organizational development. Drawing upon a quantitative approach, a structured questionnaire was administered to 386 civil servants to collect data. The empirical analysis employed the Smart-Partial Least Square (SmartPLS) software to examine the structural equation model. The findings substantiate the proposed model, revealing that decision-making partially mediates the association between leader power and organizational development. Interestingly, the direct effects of leader power and decision-making on organizational development are found to be more significant. These results underscore the paramount significance of effective decision-making and shed light on the nuanced interplay between leader power, the decision-making process, and organizational development.